Solve for f.

–7f − 9 = 9 − 4f

f =

Answers

F= 6.
-7f -9=9-4f
3f-9=9
3f=18
F=6

\boxed{f = -6}

Step-by-step explanation:

=    - 7f - 9 = 9 - 4f \\  \\  =    - 7f + 4f - 9 = 9 \\  \\  =    - 3f = 9 + 9 \\  \\  =    - 3f = 18 \\  \\  =   3f =  - 18 \\  \\  =   f =  -  \frac{18}{3}  \\  \\  =   f =  - 6

\boxed{f = -6}

Step-by-step explanation:

=    - 7f - 9 = 9 - 4f \\  \\  =    - 7f + 4f - 9 = 9 \\  \\  =    - 3f = 9 + 9 \\  \\  =    - 3f = 18 \\  \\  =   3f =  - 18 \\  \\  =   f =  -  \frac{18}{3}  \\  \\  =   f =  - 6



Do you know the answer?

Other questions on the subject: Mathematics